Early or First Aid Administration Versus Late or In-hospital Administration of Aspirin for Non-traumatic Adult Chest Pain: A Systematic Review - Djarv, Therese (Cureus, 2020)
Chest pain is a common symptom of acute coronary syndrome, including myocardial infarction (MI). Treatment with antiplatelet agents, such as aspirin, improves survival, although the ideal dose is uncertain. It is unknown if outcomes can be improved by giving aspirin early in the course of MI as part of the first-aid management as opposed to late or in-hospital administration. We searched the Medline, Embase, and Cochrane databases and used Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) and Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) for determining the certainty of evidence. We included studies in adults with non-traumatic chest pain, where aspirin was administered early (within two hours) following the onset of chest pain as part of first-aid management as compared with late or in-hospital administration (The International Prospective Register of Systematic Reviews (PROSPERO) registration number: CDR153316). From 1470 references, we included three studies (one randomized controlled trial (RCT) and two non-RCTs). Early administration (median 1.6 hours or pre-hospital) was associated with increased survival as compared with late administration (median 3.5 hours or in-hospital) at seven days; risk ratio (RR) 1.04 (95% CI 1.03-1.06), 30 days RR 1.05 (95% 1.02-1.07), and one-year RR 1.06 (95% CI1.03-1.10). The evidence is of very low certainty due to limitations in study design and the imprecision of the evidence. This systematic review would suggest that the early or first-aid administration of aspirin to adults with non-traumatic chest pain improves survival as compared with late or in-hospital administration.